Implementasi Kebijakan Dalam Menyelesaikan Konflik (Studi Di Area Hak Pengusahaan Hutan Tanaman Industri PT. Sinar Mas Grup) Di Kabupaten Pelalawan - Prihatin, Panca Setyo; Syaprianto, Syaprianto (Sisi Lain Realita, 2017)
This study aims to see the implementation of policies in resolving conflicts in the area of Industrial Plantation Forest Concession Rights of PT. Sinar Mas Group in Pelalawan District, the conflict must be quickly resolved so as not to cause greater problems, the seriousness of the government is needed. In this study researchers used the implementation theory according to Grindle and used qualitative analysis methods with the aim of describing, analyzing and attempting to elaborate policies and solutions in conflict resolution by interviewing directly and in depth the key informants who were considered most knowledgeable using purposive sampling technique. The findings of this study indicate that the implementation of policies in resolving conflicts in the area of Industrial Plantation Forest Concession Rights of PT. The Sinar Mas Group in Pelalawan District has not been implemented properly, so it is expected that the government will be more active in resolving the conflict, one of them is by revising the existing policy and the government must prioritize the principle of consensus by involving the company and community leaders around the company that.